Cognitive impairment across the schizophrenia spectrum: a comparative neuropsychological study - He, Xiao-Yan; Wei, An-Pei; Huang, Zhuo-Hui; Wang, Fei; Guo, Li Li; Hou, Cai-Lan (Frontiers in Psychiatry, 2025)
IntroductionCognitive impairment represents a core feature of schizophrenia spectrum disorders, predating psychosis onset and persisting throughout illness progression. This cross-sectional study systematically evaluates neurocognitive functioning across five critical populations: multi-episode chronic schizophrenia (MECS), first-episode psychosis (FEP), clinical high-risk (CHR) individuals, first-degree relatives (FDR), and healthy controls (HC).MethodsA comprehensive neuropsychological battery was administered to 366 participants: 40 MECS, 94 FEP, 54 CHR, 80 FDR, and 98 HC. Assessments included: Processing speed: Trail Making Test-A (TMT-A), Digit Symbol Coding Test (DST). Attention: Continuous Performance Test (CPT). Verbal memory: Hopkins Verbal Learning Test-Revised (HVLT-R).Visual memory: Brief Visuospatial Memory Test-Revised (BVMT-R). Executive function: Stroop Color and Word Test (SCWT). Group differences were analyzed using Analysis of Covariance (covariates: age, education) with Bonferroni correction, supplemented by multinomial logistic regression.ResultsA stepwise gradient of impairment emerged across the schizophrenia spectrum (HC > FDR > CHR > FEP > MECS), with significant between-group differences (p<0.001) persisting after covariate adjustment. Key findings revealed: 1. MECS demonstrated cognitive deficits, showing significantly poorer verbal memory (HVLT-R:d=0.65:p<0.001) and executive function (Stroop words:d=0.56, p=0.003,Stroop color:d=0.60, p=0.006,Stroop words color:d=0.46, p=0.03) performance than FEP.2. CHR exhibited intermediate impairment: - Outperformed FEP in processing speed (TMT-A: d=0.45, p=0.009, DST: d=065, p=0.001), attention (CPT: d=0.42, p=0.03), and executive function (Stroop words color: d=0.39, p=0.03). - Underperformed FDR across all domains except visual memory (BVMT-R: d=0.16, p=0.92).3. FDR showed subtle but consistent deficits relative to HC (all tests p<0.05), with largest effects in visual memory (BVMT-R: d=0.99, <0.001).DiscussionThese findings support a stratified continuum of cognitive impairment across schizophrenia progression. While chronic patients manifest generalized deficits, at-risk populations demonstrate distinct profiles: FDR display subclinical vulnerabilities, whereas CHR show intermediate impairment exceeding familial risk but preceding acute psychosis. The differential trajectory of verbal memory and executive function deficits from FEP to MECS suggests progressive deterioration in higher-order cognitive domains. These gradient patterns may inform stage-specific cognitive interventions across the schizophrenia spectrum.